Individual adaptation in cross-country skiing based on tracking during training conditions - Martin, S. A.; Hadma, R. M. (Sports, 2019)
Research on heart rate (HR), mean arterial pressure (MAP) and blood pressure (BP) during specific training stages is less common in endurance athletes, whereas resting BP and HR are less studied in relationship to HRmax. In the current study, the objective was to conduct a medium-term HR, BP and MAP analysis while tracking individual training outcomes. The study was conducted during the 2017-2018 season, over 43 days and 1033 km of training volume, on 12 competitive male cross-country ski athletes. One VO2max test was performed 10 days before the start of the training program. After the test, training volume and intensity was preset for each subject, according to the general training methodology. Early morning HR, MAP and BP measurements were taken as part of the basic functional analysis. Training volume was correlated to both distance (p = 0.01, r = 0.85, CI95% = 0.80 to 0.88) and training HR%, namely the percentage of HRmax (p = 0.01, r = -0.47, CI95% = -0.58 to -0.34). Both the supine (sHR) and orthostatic HR (oHR) values were significantly correlated with the training intensity. We obtained a significant correlation between sHR and oHR values and the training objective (p = 0.01). An increased oHR was correlated to high intensity training activity (HIT) during the second training session (p = 0.01). Heart rate and blood pressure measurements represent predictive functional adaptation parameters over different training phases. We highlight a link between sHR, oHR, MAP data, and the athletes` ability to perform in lower effort zones during physical exertion. However, we failed to validate MAP as a cardiovascular stress indicator following high intensity training.